The prognostic role of PD-L1 expression for survival in head and neck squamous cell carcinoma: A systematic review and meta-analysis. (November 2018) - Yang, Wei-fa; Wong, May C.M.; Thomson, Peter J.; Li, Kar-Yan; Su, Yu-xiong
Highlights: PD-L1 detected by IHC was not a robust prognostic factor for survival in HNSCC. PD-L1 expression might predict progression-free survival in advanced HNSCC. The combined roles of PD-L1 and CD8+ tumor-infiltrating T cells in HNSCC should be further elucidated. Abstract: Background: Programmed death-ligand 1 (PD-L1) is an immune checkpoint that is primarily located on the surface of tumor cells. PD-L1 expression detected by immunohistochemistry (IHC) assays has been widely studied to predict survival outcomes in head and neck squamous cell carcinoma (HNSCC) recently. We aimed to review comprehensively the prognostic role of PD-L1 expression for survival in HNSCC. Methods: We systematically searched PubMed, Embase, Web of Science, Cochrane Library and Scopus to identify studies investigating the prognostic role of PD-L1 expression in HNSCC. All studies published before March 31, 2018 were screened. Included studies were assessed using the Quality in Prognosis Studies (QUIPS) tool. Data were extracted and overall survival (OS), disease-free survival (DFS), progression-free survival (PFS), disease-specific survival (DSS) were combined and presented as hazard ratios (HR) with 95% confidence interval (CI) using the generic inverse-variance method. Results: Twenty-three studies with 3105 patients were analysed. The overall positive rate of PD-L1 in HNSCC was 0.42 (95% CI: 0.36–0.48). There was no significant difference between PD-L1-positive and -negative HNSCC patients in OS (HR: 0.98; 95% CI: 0.71–1.37; p = 0.93), DFS (HR: 1.07; 95% CI: 0.68–1.70; p = 0.76), and DSS (HR: 0.90; 95% CI: 0.63–1.29; p = 0.56). An improved PFS was observed in patients with positive PD-L1 expression (HR: 0.71; 95% CI: 0.55–0.93; p = 0.01). In patients with low CD8+ tumor-infiltrating T cells, a poorer OS was detected in patients with positive PD-L1 expression (HR: 1.90; 95% CI: 1.07–3.36; p = 0.03). Patients with HPV-positive HNSCC were associated with increased PD-L1 expression (OR: 1.99; 95% CI: 1.50–2.64; p < 0.001). However, PD-L1 expression showed no significant benefit on OS in HPV-positive HNSCC (HR: 1.04; 95% CI: 0.65–1.65; p = 0.88). Conclusions: PD-L1 expression detected by IHC was not recommended to predict survival in HNSCC patients. However, the positive PD-L1 expression might predict better PFS in patients with advanced HNSCC. The combined effects of PD-L1 expression and CD8+ tumor-infiltrating T cells should be further elucidated.